A review on the land expropriation and its management in China - LIU Wei-dong; LOU Li-ming (浙江大学学报. 农业与生命科学版)
According to the rules and regulations currently in operation in China, land expropriation is a government activity by which some collective agricultural land is compulsively transformed into state-owned land to meet the needs of social development and economic construction. Of course, the peasants who lose their land should be given reasonable compensation for their loss and their living or job properly rearranged. As a matter of fact, the price of expropriated land paid by the government was quite frequently brought down to a level lower or much lower than it actually deserved. So it was not rare that the collective interests of the related rural business organization and the personal property right of the related individual peasants were substantially harmed by land expropriation. One of the outcomes was the complete rejection of the present system of land expropriation. Accordingly, the problem of elaborating a fair as well as reasonable, highly effective and feasible system of land expropriation has caused considerable attention among academic researchers and become a major concern of the government decisions. In this paper, we will deal with the various reflections arose from and perplexities involved in this problem, the views and suggestions of the authors will also be presented. Government should keep on the unification of activity, limit the land use change from rural into non-agricultural, increase the land compensation standard, and enhance public participation and supervision in the land expropriation processes.